2008
DOI: 10.1053/j.gastro.2008.01.075
|View full text |Cite
|
Sign up to set email alerts
|

Liver, Muscle, and Adipose Tissue Insulin Action Is Directly Related to Intrahepatic Triglyceride Content in Obese Subjects

Abstract: Background & Aims-Nonalcoholic fatty liver disease is associated with insulin resistance and diabetes. The purpose of this study was to determine the relationship between intrahepatic triglyceride (IHTG) content and insulin action in liver (suppression of glucose dioduction), skeletal muscle (stimulation of glucose uptake) and adipose tissue (suppression of lipolysis) in non-diabetic, obese subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

24
417
4
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 523 publications
(446 citation statements)
references
References 39 publications
24
417
4
1
Order By: Relevance
“…Nevertheless, cardiovascular diseases (CVD), including coronary heart disease and non-ischemic cardiomyopathy, are the leading cause of death in patients with NAFLD [1]. The pathophysiological hallmark of NAFLD is insulin resistance (IR), and the increase in intrahepatic triglycerides (IHTG) is directly related to the impairment of insulin action in the liver, skeletal muscle, and adipose tissue of obese subjects [3][4][5]; recently, the Framingham Heart Study has shown that IHTG content predicts the glucose and lipid abnormalities of the metabolic syndrome independently of visceral fat [6,7]. Furthermore, liver fat content is an independent indicator of myocardial IR and impaired coronary functional capacity in diabetic patients [8], thus suggesting that NAFLD is not merely a marker, but may be actively involved in the onset and progression of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, cardiovascular diseases (CVD), including coronary heart disease and non-ischemic cardiomyopathy, are the leading cause of death in patients with NAFLD [1]. The pathophysiological hallmark of NAFLD is insulin resistance (IR), and the increase in intrahepatic triglycerides (IHTG) is directly related to the impairment of insulin action in the liver, skeletal muscle, and adipose tissue of obese subjects [3][4][5]; recently, the Framingham Heart Study has shown that IHTG content predicts the glucose and lipid abnormalities of the metabolic syndrome independently of visceral fat [6,7]. Furthermore, liver fat content is an independent indicator of myocardial IR and impaired coronary functional capacity in diabetic patients [8], thus suggesting that NAFLD is not merely a marker, but may be actively involved in the onset and progression of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that intra-hepatic and intra-myocellular lipid contents are closely related with insulin resistance and an adverse metabolic phenotype. [5][6][7] Thus, what seems to be more important than generalized adiposity is where the body fat is located. However, despite the importance of ectopic fat deposition, the association between fat deposition within muscle or liver and atherosclerosis or cardiovascular disease is yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Hepatic lipid accumulation contributes to known metabolic alterations, such as insulin resistance, hyperglycemia, and hyperlipidemia. [5][6][7] NAFLD can be further divided into two major subtypes, which seem to have different outcomes: simple steatosis (NAFL) without liver inflammation or injury and nonalcoholic steatohepatitis (NASH). 8 NASH leads to liver cirrhosis 9 and to increased mortality more often than NAFL.…”
mentioning
confidence: 99%